How to Objectively Measure The Quality of Sleep - Diego Liberati (Journal of Sleep And Sleep Disorder Research, 2018)
A methodological overview of objective sleep quality measurement compares actigraphy, polysomnography, and novel sensors, with notes on validity and real‑world use.
Keywords: Sleep Quality